INNOVATIVE APPROACHES IN MATHEMATICS EDUCATION: ENHANCING STUDENT UNDERSTANDING AND ENGAGEMENT - Imroatus Sholihah, Farid (Berajah Journal, 2024)
Mathematics education has long been a subject of interest due to its critical role in developing logical thinking and problem-solving skills. Despite its importance, many students struggle to grasp mathematical concepts, leading to widespread math anxiety and disengagement. This paper explores innovative teaching approaches that can improve student understanding and foster engagement in mathematics. Through the integration of technology, active learning strategies, and contextualized problem-solving, educators can create a more interactive and meaningful learning environment. Additionally, differentiated instruction and collaborative learning are identified as key methods to cater to diverse student needs. The research highlights how these strategies have positively impacted student achievement and attitudes toward mathematics. This paper aims to provide a comprehensive overview of effective methods in mathematics education that can be adopted by educators to enhance both teaching and learning outcomes.